Service evaluation in public and school libraries: a case study using LIBQUAL+® - Furnival, Ariadne Chloe; Pinto, Euzébio Luiz (Faculdade de Filosofia e Ciências, 2016)
We report case study research that was carried out to assess quality in two public libraries and one school-community library in a municipal Integrated Library System in the state of São Paulo, by surveying the perception of their users regarding service and infrastructural aspects. An instrument adapted from that of LIBQUAL + ® and semi-open interview techniques, based on Benevox® software questions were used. The research was motivated by the desire of the studied Integrated Library System (SIBI) to conduct a thorough evaluation of service and infrastructure of their libraries and to capture the perception of the public regarding the services, as well as determining the performance of the LIBQUAL + ® instrument with a much more diverse audience, compared to the university libraries that applications of the instrument typically involve. Data analysis highlighted the need for several improvements related to the information control and infrastructure of libraries; while on the other hand, a good perception of services by the public was revealed. However, the context of data collection revealed limitations of the LIBQUAL + ®instrument, both in its application with the type of public involved and regarding specific aspects of the libraries that the instrument could not cover. The qualitative data generated from the semi-open interviews therefore complemented the LIBQUAL-type data. . The statistical manipulation of this qualitative data generated allowed a more broad approach for the evaluation of the library dimensions considered by LIBQUAL + ® , opening up the possibility for the development and use of new assessment techniques for services in information units.